The logistics and supply chain toolkit over 100 tools for transport, warehousing and inventory management - Richards, Gwynne; Grinsted, Susan (KoganPage, 2024)
"The Logistics and Supply Chain Toolkit provides practical tools for warehouse, inventory and transport managers and students to help them tackle the challenges of logistics and supply chain management. It is full of practical ideas and information to optimise the management of logistics and supply chain processes. The Logistics and Supply Chain Toolkit offers solutions and plans spanning across a variety of sub-disciplines such as warehousing, logistics, supply chain management, inventory and outsourcing. Each toolkit addresses key principles within its area of discipline, providing the reader with a precision approach to be used in complex and sensitive circumstances. The toolkit presents a number of major management tools such as Fortna's Product Flow Smart Design, SMART, DMAIC and Gantt charts. General management, performance management and problem-solving tools have also been included to provide a broader, transferable scope of tools for the reader"--